Bank and Non‐Bank Financial Deepening and Economic Growth: The Nigerian Experience (1981–2010). (8th October 2013) - Iyoboyi, Martins
Abstract The paper aimed at empirically investigating the impact of financial deepening on the growth of an economy, with particular emphasis on Nigeria over the period 1981–2010. Financial deepening was segregated to capture both bank and non‐bank financial variables, because both are imperative to economic activities. The study therefore combined a proxy of banking sector development with stock market development to capture the influence of financial deepening on growth. The analysis is based on the bound testing approach to cointegration. The empirical results confirm cointegrated relationship between economic growth and financial deepening. The study also showed that, in the period of study, while there is bidirectional causality between bank financial deepening and economic growth, causality runs from economic growth to non‐bank financial deepening. The results of the investigation are in favour of the finance‐growth cum growth‐finance hypothesis. For the period under study, Nigeria's economic growth is sensitive to changes in financial deepening, past level of growth and the openness of the economy. It is therefore imperative that policies which seek to deliberately increase financial depth be vigorously pursued, in order to stimulate growth and consequently further deepen the financial sector of the economy.